ANALISIS EFEKTIVITAS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI MADRASAH IBTIDAIYAH KECAMATAN MANYAR KABUPATEN GRESIK - Iga Sri Moerni (COMMUNITY OF RESEARCH LABORATORY SURABAYA)
The event that many BOS funds (School Operational Assistance) were hampered as well as mass and systematic corruption in administering BOS funds due to delays in the distribution and poor supervision of the system prompted the authors to research analysis of how to effective BOS fund management is. Research object: Ibtidaiyah Madrasah Institute in Manyar District - Gresik Regency. Problem formulation: What is the effectiveness of managing BOS funds and what factors influence it. Research Objectives: To analyze the effectiveness of BOS fund management and analyze the factors that influence it. Research methods: This study uses a descriptive qualitative approach, with informants from school principals, school principals, and school treasurers in 31 MIs. Data collection using questionnaires, interviews, observations, and documentation. Data analysis using descriptive qualitative. Research findings: (1) Management of BOS funds in MI has been carried out effectively, (2) 4 factors influence the effectiveness of management of BOS funds, namely planning, allocation, distribution, and reporting-responsibility, (3) Distribution factors have a dominant influence on management effectiveness BOS funds. Suggestion: Further socialization is needed for all committees, teachers, administrative staff, and parents so that BOS funds can be channeled better.